Clinical observation on treatment of cough during pregnancy with modified Baihe Gujin Decoction - Liyuan Fu; Jing Lin; Meiyu Yao; Fang Niu; Fenglan Ma; Ling Wang (World Scientific Publishing, 2020)
Background: To investigate the clinical effect of modified Baihe Gujin Decoction in treatment of cough during pregnancy. Methods: A total of 31 pregnant women with cough were recruited from First Affiliated Hospital of Heilongjiang University of Traditional Chinese Medicine and Shanghai Qingpu District Hospital of Traditional Chinese Medicine from February 2016 to June 2020. The patients were treated with modified Baihe Gujin Decoction for two weeks according to their unique symptoms and signs. The cough symptoms were evaluated and the symptom scores were calculated at Day 0 (time of enrollment), Day 7, and Day 14, respectively. Results: Of 31 cases, 4 cases were clinically cured and 24 cases showed marked improvement, with 3 cases showing no improvement. Conclusions: Modified Baihe Gujin Decoction can significantly improve the symptoms of cough during pregnancy.